Assessing soil CO2 emission on eucalyptus species using UAV-based reflectance and vegetation indices - Rossi, Fernando Saragosa [UNESP]; Della-Silva, João Lucas; Teodoro, Larissa Pereira Ribeiro; Teodoro, Paulo Eduardo; Santana, Dthenifer Cordeiro; Baio, Fábio Henrique Rojo; Morinigo, Wendel Bueno; Crusiol, Luís Guilherme Teixeira; La Scala, Newton [UNESP]; da Silva, Carlos Antonio (Springer Nature, 2024)
Eucalyptus species play an important role in the global carbon cycle, especially in reducing the greenhouse effect as well as storing atmospheric CO₂. Thus, assessing the amount of CO₂ released by the soil in forest areas can generate important information for environmental monitoring. This study aims to verify the relation between soil carbon dioxide (CO₂) flux (FCO₂), spectral bands, and vegetation indices (VIs) derived from a UAV-based multispectral camera over an area of eucalyptus species. Multispectral imageries (green, red-edge, and near-infrared) from the Parrot Sequoia sensor, derived vegetation indices, and the FCO₂ data from a LI-COR 8100 analyzer, combined with soil moisture and temperature data, were collected and related. The vegetation indices ATSAVI (Adjusted Transformed Soil-Adjusted VI), GSAVI (Green Soil Adjusted Vegetation Index), and SAVI (Soil-Adjusted Vegetation Index), which use soil correction factors, exhibited a strong negative correlation with FCO₂ for the species E. camaldulensis, E. saligna, and E. urophylla species. A Multivariate Analysis of Variance showed significance (p < 0.01) for the species factor, which indicates that there are differences when considering all variables simultaneously. The results achieved in this study show a specific correlation between the data of soil CO₂ emission and the eucalypt species, providing a distinction of values between the species in the statistical data.